Developing a hydrogel ink for creating reconfigurable 3D printed structures - Yuan, Weizhe (Nanyang Technological University, 2022)
Hydrogel has emerged as one of the most important biomaterials in biological and biomedical fields due to many superior properties, such as biocompatibility, high porosity, etc. Reconfigurability represents an appealing feature of the hydrogel structures whose shapes can be remodeled after they are printed. Existing reconfigurable hydrogel structures are mainly created by incorporating stimulus-active materials into the hydrogel precursor solution. After being crosslinked, the hydrogel structures change shapes when they are exposed to external stimuli due to the mismatch strain caused by non-uniform response to the external stimuli. However, this approach only allows the hydrogel structures to be reshaped into very limited number of configurations. In this study, we aim to develop a reconfigurable hydrogel ink. We use sodium alginate as a base material and ethanol and proanthocyanins as additives. The ethanol allows the ink to form a physical hydrogel after a structure is printed by lowering the temperature below the sol-to-gel transition temperature, while proanthocyanins will be used to boost the absorption of the near infrared laser light generated with a laser emitter. Gel-to-sol transition occurs when the local temperature is raised high enough. We have tested the effect of the additives and confirmed the existence of the sol-to-gel and gel-to-sol transitions. Our study paves a way for developing novel hydrogel ink formulations for creating many other types of hydrogel structures.